138 Non-anginal chest pain: not as benign as we would like to believe!. (16th May 2012) - George, A; Anwar, T; Advani, K; Cullington, D; John, J; Chattopadhyay, S
Abstract : Background: In the Quick Reference Guide of the clinical guidance 95 (CG95) NICE recommends that chest pain (CP) diagnosed as non-anginal (NA) should not be investigated for stable angina routinely. In the Full Guidance, it qualifies this statement suggesting that stable angina should be excluded in patients with NACP unless clinical suspicion is raised based on other aspects of the history and risk factors. In the chest pain management algorithm, however, it excludes patients with NACP in whom stable angina is suspected based on history and risk factors. This study was undertaken to assess the outcome of patients attending rapid access chest pain clinic (RACPC) and diagnosed with NACP who are likely to be discharged without further investigation as suggested by CG95. Method and Results: 1042 consecutive RACPC referrals between November 2009 and April 2011 were reviewed. Demographics, CG95 defined risk factors, CP characteristics, history of confirmed coronary artery disease (CAD), results of the exercise ECG test, management plan and outcomes (composite end point of all cause mortality, non-fatal myocardial infarction, referral/admission to hospital with CP) up to a minimum of 6 months after the index assessment were analysed. Typical, atypical and NACP were determined from CP characteristics. 622 patients without confirmed CAD were diagnosed with NACP. Following the 1st visit, 70 patients were recommended coronary angiograms (27 significant CAD, (26 revascularised, 1 treated medically), 7 refused) and 66 had myocardial perfusion scans (14 reversible/2 fixed defects). 62 (10%) patients reached an end-point (2 cancer deaths, 11 non-fatal MI, 40 readmitted and 8 rereferred with CP, 1 non-haemorrhagic stroke). Of these patients, 29 were previously investigated: 21 angiograms (10 significant CAD), 14 MPS (3 reversible/1 fixed defect). Investigations after reaching end-point showed 3 significant CAD (14 angiograms) and 1 reversible defect (5 myocardial perfsion scan). 14 others were not investigated further due to unequivocally negative exercise ECG. Only the presence of diabetes predicted the end-point (OR 5.21, 95% CI 2.67 to 10.15, p<0.0001) in a multiple logistic regression analysis using age, gender, current smoking, total cholesterol >6.47 mmol/l and diabetes as covariates. Conclusion: 47 (7.6%) patient that are to be discharged without investigation, had significant coronary artery disease. Even with a short follow-up, 10% of these patients needed medical attention for suspected cardiovascular morbidity. It may be unreasonable to discharge patients describing NACP especially diabetics.